Syntheses of 15N-labeled pre-queuosine nucleobase derivatives - Levic, Jasmin; Micura, Ronald (Beilstein Journal of Organic Chemistry, 2014)
Pre-queuosine or queuine (preQ1) is a guanine derivative that is involved in the biosynthetic pathway of the hypermodified tRNA nucleoside queuosine (Que). The core structure of preQ1 is represented by 7-(aminomethyl)-7-deazaguanine (preQ1 base). Here, we report the synthesis of three preQ1 base derivatives with complementary 15N-labeling patterns, utilizing [15N]-KCN, [15N]-phthalimide, and [15N3]-guanidine as cost-affordable 15N sources. Such derivatives are required to explore the binding process of the preQ1 base to RNA targets using advanced NMR spectroscopic methods. PreQ1 base specifically binds to bacterial mRNA domains and thereby regulates genes that are required for queuosine biosynthesis.
Keywords: heterocycles; ligands; nucleic acids; nucleobases; nucleosides; pyrrolopyrimidinones